Chemo-immunotherapy of colon cancer with focused ultrasound and Salmonella-laden temperature sensitive liposomes (thermobots) - Kalyani Ektate (Nature Portfolio, 2018)
Abstract Using attenuated Salmonella that efficiently homes in solid tumors, here we developed thermobots that actively transported membrane attached low-temperature sensitive liposome (LTSL) inside colon cancer cells for triggered doxorubicin release and simultaneous polarized macrophages to M1 phenotype with high intensity focused ultrasound (HIFU) heating (40–42 °C). Biocompatibility studies showed that the synthesized thermobots were highly efficient in LTSL loading without impacting its viability. Thermobots demonstrated efficient intracellular trafficking, high nuclear localization of doxorubicin, and induced pro-inflammatory cytokine expression in colon cancer cells in vitro. Combination of thermobots and HIFU heating (~30 min) in murine colon tumors significantly enhanced polarization of macrophages to M1 phenotype and therapeutic efficacy in vivo compared to control. Our data suggest that the thermobots and focused ultrasound treatments have the potential to improve colon cancer therapy.